Die Biedermeierzeit als verfallenes Forschungsmonument? - Venzl, Tilman; Zimmermann, Yvonne (Scientia poetica, 2017)
This article examines how older research on Biedermeier is evaluated in current discourse, taking as its focus the example of recent studies on Annette von Droste-Hulshoff. One can observe a refusal of earlier knowledge claims, those that are most notably linked to the literary scholar Friedrich Sengle, which can be ascribed to various overlapping motives. Besides the criticism of specific research results, a rejection of Sengle himself can be seen, which is most likely a consequence of his personal, academic, and political actions during the Nazi era and in West Germany. However, Sengle’s works nevertheless continue to offer promising insights for current research, as is exemplified in an examination of Droste-Hulshoff’s author’s poetics. Ultimately, the article argues for a differentiated evaluation, i. e. one that is based on the history of German literary studies, older research on Biedermeier in general, and Sengles Biedermeier Period (Biedermeierzeit) in particular.
Gesehen am 28.02.2018